(untitled) (Indian Journal of Animal Production and Management, 2024)
A field study was done to know the cost and returns of different buffalo breeds among the landless, small farmer and commercial milk producers in Guntur district of A.P. It was observed that the average cost of milk production per litre was significantly (P≤0.01) lower in Murrah buffaloes (Rs. 26.48) than that in graded Murrah buffaloes (Rs. 27.56) and local buffaloes (Rs. 30.55). The average gross income was significantly (P≤0.01) higher in Murrah (Rs. 411.80) per day than that in graded Murrah (Rs. 331.62) and local buffaloes (Rs. 254.53). The average net income was significantly (P≤0.01) higher in Murrah (Rs. 144.40) than that in graded Murrah (Rs. 114.56) and local buffaloes (Rs. 72.99). The share of total feed cost in Murrah, graded Murrah and local buffalo was 59.29, 61.61 and 63.17 per cent, respectively. The share of total labour cost in Murrah, graded Murrah and local buffalo was 17.78, 18.13 and 17.81 per cent, respectively, in the total maintenance cost (gross cost) of buffaloes.